Characterization and provenance of building materials from the Roman pier at San Cataldo (Lecce, Southern Apulia, Italy): A lithostratigraphical and micropaleonthological approach - Sammarco, Mariangela; Margiotta, Stefano; FORESI, LUCA MARIA; Ceraudo, Giuseppe (2015)
This study deals with the characterization of building materials used in a monumental pier of Roman age, located at San Cataldo, the main coastal harbour of the Roman town of Lupiae, modern Lecce (Southern Italy). In the manufacture of the outer curtains three different lithologies have been recognized, all comprised in Pietra Leccese Formation, which crops out in a broad geographical area of Salento Peninsula. Microfossils recovered from limestone blocks are used to suggest a provenance for the source-rock. Microfossils include planktonic foraminifera characteristic of the upper Miocene (Tortonian-Messinian) foraminiferal MMi11 (Neogloboquadrina acostaensis Biozone) and MMi13 (Globorotalia miotumida Biozone) biozones. The analysed lithic materials show biostratigraphical characteristics very similar to some samples from Acaya-Strudà zone (some 10 km South-West from the ancient harbour): comparative analysis has been performed, supporting a clear identification of the geological origin of limestone blocks. In hydraulic concrete different lithic materials have been used and mixed with a strong mortar. Macroscopic field observation clearly define that limestone clasts, variable in size, derive from the Pliocene Uggiano la Chiesa Formation, that widely crops out locally at San Cataldo; granular fractions of mortar probably derive from beaches and/or sandy dunes, available in the surrounding area, as well.